Critical Analysis of Gitanjali - Hina Saba (بازیافت, 2020)
Rabindrenath Tagore's Gitanajli depicts the spiritual and emotional voyage of the poet towards the Supreme Being. It is a collection of devotional songs in which Tagore offers his prayer to God. But the  religious fervor of these songs never mars the poetic beauty them. Instead what makes them appealing to the readers are its profoundness  expressed with simplicity optimism and spiritual affirmation, richness and variety, humanization of divine, use of domestic image and symbols and metaphoric elements.